Perspectives and experiences of community-dwelling older adults who experience falling: A qualitative meta-synthesis - Huimin Jiang; Haobin Yuan; Stephen Tee; Oi Ching Bernice Lam Nogueira (Elsevier, 2024)
Objectives: This study aimed to systematically review and synthesize the perspectives and experiences of community-dwelling older adults who experience falling, to inform the subsequent development of fall prevention and management interventions, and to provide recommendations for healthcare policy and practice. Methods: The review was a qualitative meta-aggregation study following the JBI qualitative systematic review methodology. Databases searched included Medline (through PubMed), CINAHL, PsycINFO, Embase, and the Web of Science. Peer-reviewed articles published in the English language from January 2010 to May 2023 were retrieved. The JBI Qualitative Assessment and Review Instrument (JBI-QARI) was used to assess the quality of the methodology. The ConQual ranking system was used to establish confidence in the synthesized findings. The protocol was registered with PROSPERO (CRD 42023421789). Results: This review included ten qualitative studies with an overall quality score of 60%-90%. Data extracted from eligible studies resulted in 59 findings, which were then aggregated into seven categories based on the similarity in meaning. Three synthesized findings were generated and rated as moderate for synthesized finding 2 and low for synthesized finding 1 and 3 on the ConQual score. Synthesized finding 1: Older adults experience physical injuries and pain, restricted daily activities, and limitations in social activities, reduction or loss of in independence, and have feelings of fear and helplessness. Synthesized finding 2: After experiencing a fall, older adults reflect on the cause of the fall and recognize and interpret the risk factors. Synthesized finding 3: Older adults' reflections on the causes and impact of falls reveal both positive and negative reactions. They perceive a number of strategies for coping with falls and their consequences, such as using assistive devices, correcting risk factors, seeking medical help, and receiving ongoing physical and psychological attention. Conclusions: Healthcare providers should pay attention to the feelings and experiences of older adults after falling, as well as their reflection on the causes and impacts of falling, and develop tailored plans for intervention. There is also a need for longitudinal studies to examine the longer-term impact of falls on older adults to provide insights into the stability and changes in their reflections, perceptions, attitudes, and preventive behaviors over time.